PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, TEKNOLOGI INFORMASI, REVIU LAPORAN KEUANGAN DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAH PROVINSI SULAWESI UTARA - Kalumata, Merlyn C. T.; Ilat, Ventje; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2016)
This study aims to examine the effect of human resources competence, information technology, review of financial statement and internal control system on the quality of financial statement in Government of North Sulawesi. The variables in this study consist of independent variable :human resources competence (X1), information technology (X2), review of financial statement (X3) and internal control system (X4).On the other hand, the dependent variable is the quality of financial statement (Y). Data were analyzed by multiple linear regression analysis (multiple regression). The results indicate that human resources competence, information technology, review of financial statement and internal control system simultaneously have a significant influence on the quality of financial statement. The value of the coefficient of determination shows that human resources competence, information technology, review of financial statement and internal control system simultaneously contribute to the quality of financial statement.R2 is 71.3%, it means those dependent variables affect the quality of financial statement by 71.3%. While the remaining of 28.7% is influenced by other variables which are excluded within this research. Partial test results show that information technology, review of financial statement and internal control system have a significant impact on the quality of financial statement. Human resources competence has no significant impact on the quality of financial statement. Keywords : quality of financial statement, human resources competence, information technology, review of financial statement, internal control system